Avaliação da diversidade e estrutura genética de Micoureus paraguayanus (Didelphidae) em fragmentos de mata atlântica - Guedes, Fátima Becker (Universidade Federal de São Carlos, 2008)
Habitat fragmentation is one of the main results of human alterations on nature. Understanding the biological consequences of this process is essential to reach the goal of conserving natural resources. The aim of this project was to assess levels of diversity and genetic structure of a population of the marsupial Micoureus paraguayanus, in forest remnants of a Semi-Decidual Estational Forest in the region of Pontal do Paranapanema, São Paulo. This variation was evaluated in ten microsatellite loci scored in 95 individuals sampled from six habitat fragments, including the Morro do Diabo State Forest. Genetic diversity in each subgroup was estimated by considering the average number of alleles (6,1 overall) and heterozygosity (0,488 when averaging all subpopulations). The latter was lower than values described in the literature for non-inbred populations on average. The number of alleles of three loci were also lower than what was observed for other population from the same species. So, on average, diversity was slightly lower than observed elsewhere. We detected a significant positive correlation (R = 0,087; P = 0,003) between genetic and geographic distances of populations of the fragments. The high number of migrants per generation (Nm) indicates historic gene flow between the analyzed populations. In spite of that, significant values of Fst and Rst were detected between some of the populations. A significant genetic differentiation was detected between Santa Teresa, Santa Maria and Ponte Branca. To analyze the genetic structure of this population we used the softwares Tess and Structure, which indicated tree clusters in the population of M paraguayanus sampled, which are associated with the three populations previously mentioned. These localities were the smallest and most disturbed fragments evaluated in this study and their differences probably indicate that the recent fragmentation process about 60 years could be responsible for promoting changes, by founder effect or bottleneck, in the genetic composition of the studied population.
Keywords: Genética de populações; Fragmentos florestais; Microssatélite; Conservação da natureza; Fragmentação; Micoureus paraguayanus; Fragmentation; Microsatellite; CIENCIAS BIOLOGICAS::GENETICA